Manajemen Kurikulum Pelatihan Tilawah di TPQ Nurul Furqon An-Nuriyah Surabaya - Eli Masnawati; M. Muhaimin (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to determine the curriculum management at TPQ Nurul Furqon An-Nuriyah Surabaya regarding its recitation training activities. This research uses a descriptive qualitative method, namely collecting data by means of observation, interviews and documentation. The main focus of the research is to identify the curriculum management strategies implemented, the effectiveness of teaching methods, and the impact of training on students' abilities